If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3(21 + -3a) = 6 + -1a (21 * 0.3 + -3a * 0.3) = 6 + -1a (6.3 + -0.9a) = 6 + -1a Solving 6.3 + -0.9a = 6 + -1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'a' to each side of the equation. 6.3 + -0.9a + a = 6 + -1a + a Combine like terms: -0.9a + a = 0.1a 6.3 + 0.1a = 6 + -1a + a Combine like terms: -1a + a = 0 6.3 + 0.1a = 6 + 0 6.3 + 0.1a = 6 Add '-6.3' to each side of the equation. 6.3 + -6.3 + 0.1a = 6 + -6.3 Combine like terms: 6.3 + -6.3 = 0.0 0.0 + 0.1a = 6 + -6.3 0.1a = 6 + -6.3 Combine like terms: 6 + -6.3 = -0.3 0.1a = -0.3 Divide each side by '0.1'. a = -3 Simplifying a = -3
| 5r+7s+70t=48 | | 3d+12=16.95 | | -9x+6x+y= | | 3x^2+3y^2-3x-3y-5=0 | | 0.6(x+80)+0.8x=97 | | b(a-7)+3(7-2)=0 | | -16-10.2g=-17.7g+16.85 | | -2x+14y=-18 | | 6x-27=4x-15 | | 5+4[(3r+s)-(3r-s)]= | | 15-2*4(6-3)= | | x+(3x)=200 | | k/2-7=37 | | x+(x+3)=200 | | 2x^9y^7+8x^7y^6+14xy= | | ax+3=-7 | | 3x+8/7+x+23/4=13 | | 9x-6=4x+12+12 | | 4-z=-4 | | 6x-44=3x-26 | | 15-2(x-3)=31 | | -8(n+7)=4(1+n) | | -21x+71=-14x+36 | | 14+3x=6x+-7 | | 5x-8x+5x= | | 2.8+10.5+9=x | | 3x+x+6=2x+16 | | 4x+8x=-4 | | 0.5b+4=150+1p | | -2.6+2a=12 | | 2(x-8)+9=2x+3 | | 6p-4=26 |